Genetic variability of sotol (Dasyrylion cedrosanum) populations in the Mexican Coahuila southern area - Rentería, Norma Paola Meléndez; Padilla, Veronica; Lozano, Gerardo Gaona; Aguilar, Cristobal Noe; Rodríguez-Herrera, Raúl (Plant Breeding and Seed Science, 2012)
In the Chihuahuan desert area, in Mexico, exist an endemic plant denominated Sotol (Dasylirion spp); which is used by rural producers to manufacture a liqueur named Sotol. This beverage has origin denomination but it industrial application has lack scientific reports, as well as the plant genetic information. This is the first study about ecological distribution of sotol plants and, may be, a first step to continue the scientific investigation of a Mexican endemic plant, with many potential industrial applications. In this paper, we used AFLP molecular markers to calculate population genetics parameters as genetic diversity, a conglomerate analyses, poblational structure based in Wright´s statistics and analysis of molecular variance. Differences in soil composition and weather conditions, of the sampling region, may affect sotol plants growth and their morphologic characteristics; as consequence the organisms generate ample genetic variability, which ensures the species permanence. Genetic diversity values were similar to the average for cross-pollinated plants, while the heterozygosis detection was deficient; Wright statistics suggest plants genetics interchange in the subpopulation; AMOVA found significant differences within and between collections. These results help us to maintenance the genetic diversity, in order to prevent potential extinction and guarantee sustainable development; the preservation of the endemic plants is necessary to the ecosystems conservation and after Sotol origin denomina- tion, by the Mexican government, the importance of D. cedrosanum plants was increased.